The Use of Cell-Free Xenopus Extracts to Investigate Cytoplasmic Events - Gibeaux, Romain; Heald, Rebecca (Cold Spring Harbor protocols, 2019)
Experiments using cytoplasmic extracts prepared from eggs have made important contributions to our understanding of the cell cycle, the cytoskeleton, and cytoplasmic membrane systems. Here we introduce the extract system and describe methods for visualizing and manipulating diverse cytoplasmic processes, and for assaying the functions, dynamics, and stability of individual factors. These in vitro approaches uniquely enable investigation of events at specific cell cycle states, including the assembly of actin- and microtubule-based structures, and the formation of the endoplasmic reticulum. Maternal stockpiles in extracts recapitulate diverse processes in the near absence of gene expression, and this biochemical system combined with microscopy empowers a wide range of mechanistic investigations.